“Where Does This World End?” Space, Time and Image in Harun Farocki’s Parallel I-IV - Synenko, Joshua (Imaginations, 2023)
Harun Farocki’s last completed installation film, Parallel I-IV, opens with a collection of video game landscapes grouped together by elements of earth, fire, water, and air, engaging a non-vococentric film essay style to reflect upon material transformations that occur through digital images. Farocki develops a unique curatorial approach to express both the power and the limits of digital image construction and the creative process, and emphasizes sharp historical perspectives. By challenging the dyad of realism and simulation and their associated narrative conventions, whether through film, video games, or art exhibits, Farocki’s brand of essay film provides critical insights into the affective and sociotechnical dimensions of the imaged world.